PESAN MAKNA FOTO BUDAYA PADA MEDIA DARING - Arifin, Muhammad Arifin (Annaba: Jurnal Ilmu Jurnalistik, 2020)
The aim is to find out what meanings are contained in journalistic photos in West Java Cultural Photos in the June 2022 Edition of the Arts, Culture and Entertainment Rubric of Antarafoto.com concerning Culture and Entertainment Arts in West Java. This research is a qualitative interpretive research. The method used in this study is Roland Barthes' semiotic analysis. The results of this study are that all photos on Antarafoto.com Online Media have denotative meanings, connotations and myths that operate in them. The meaning of the denotation contained in the photo can be seen from the object displayed and the signs that appear from the photo so that it shows meaning. The connotation meaning of photojournalism in research can be seen from the photo production process.